Mind over mood change how you feel by changing the way you think - Greenberger, Dennis; Padesky, Christine A. (The Guilford Press, 2016)
"Discover simple yet powerful steps you can take to overcome emotional distress...and feel happier, calmer, and more confident. This life-changing book has already helped more than 1,000,000 readers use cognitive-behavioral therapy...one of today's most effective forms of psychotherapy...to conquer depression, anxiety, panic attacks, anger, guilt, shame, low self-esteem, eating disorders, substance abuse, and relationship problems. Revised and expanded to reflect significant scientific developments of the past 20 years, the second edition contains numerous new features: expanded content on anxiety; chapters on setting personal goals and maintaining progress; happiness rating scales; gratitude journals; innovative exercises focused on mindfulness, acceptance, and forgiveness; new worksheets; and much more, "...